Can a patient with diabetic neuropathy be treated effectively? - Wolny, Małgorzata (Lekarz POZ, 2017)
Diabetic neuropathy is the most common complication of diabetes, which can lead to the development of the diabetic foot. The damaging effect of hyperglycaemia is observed both in the sensory-motor system and in the autonomic system. Neuropathy often occurs asymptomatically, and sometimes symptoms are uncharacteristic. Therefore, doctors should look for it actively. Based on four cases, the clinical presentation of this complication has been reported, and the possibility of causative treatment with alpha-lipoic acid and benfotiamine has been shown to be highly effective, particularly at an early stage of this complication when structural neuronal damage has not yet occurred.